Information and Communication Technology and Knowledge Sharing: a Literary Referential Study - Bin Maalawi, Turki; Rahman Obaid, Abdul (International Journal for Applied Information Management, 2022)
This study examines "information and communication technology and knowledge sharing" articles. It discusses the topic's literary relevance. Researchers examined research, studies, and Arab and global trends. The study read books. Originally, scientific databases tracked the expansion of ICT in Arab and foreign intellectual output. The first computer, the IBM 7001, was released in the mid-1970s, igniting the expansion of information and communication technology (ALTAIR). Then followed a study on ICT's impact on businesses. It was detected 7.5 million times between 1999 and 2020. 21 studies centered on the Arab world. Information sharing via research and monitoring was also explored in the study. Wilson investigated knowledge sharing to improve organizational performance in 1983. From 1980 to 2020, the number of citations for knowledge sharing in research titles in scientific articles continuously increased, reaching over a thousand. The notion of information technology and knowledge sharing developed in 1990, when Hendersk said that knowledge sharing needed information and communication technology. Robert Yinks et al. examined IT & K in 1991 AD. This study addresses ICT and knowledge sharing. From 1991 to 2020, the digital index of "information and communication technology and knowledge sharing" reveals a lot of international research on the issue. From 2005 to 2017, several studies on the same topic were presented at conferences, workshops, and scholarly forums. These studies emphasized IT and knowledge transfer. An international study on public organizations exists. The Internet, intranet, extranet, and other ICT have been studied for their influence on knowledge exchange. Other studies linked ICT to corporate culture, performance, job happiness, organizational justice, communication, and other management necessities. Another study examined how ICT may promote knowledge sharing. Some studies looked at social media's impact on knowledge sharing.